The Role Of Humanitarian Law In Protecting Humanitarian Workers In Conflict Zones - Anisa, Darania; Dalimunthe, Nur Halimah (Universitas Islam kadiri, 2026)
International humanitarian law (IHL) has an important role in providing protection for individuals involved in humanitarian assistance, especially humanitarian workers operating in conflict zones. Humanitarian workers are often targeted in armed conflicts, which threatens their safety in carrying out their humanitarian duties. This research aims to explore how IHL can provide legal protection for humanitarian workers, both in the context of international law and practice in the field. Drawing on the Geneva Conventions and Additional Protocols, as well as international court decisions, this article analyzes the challenges facing humanitarian workers in conflict zones and the legal steps that can be taken to improve their protection. The findings of this research show that despite clear protections in international law, effective implementation is often hampered by legal violations occurring on the ground, lack of law enforcement, and uncertainty about the status of humanitarian workers. Therefore, strengthening international cooperation, increasing awareness of humanitarian law, and stricter law enforcement mechanisms are urgently needed to protect humanitarian workers in conflict zones.